PANDEMIC EFFECT ON MULTIMODAL MOBILITY CHANGE - Muhamad Idris Rauf; Nurul Khasanah; Siti Hotijah; Marwati Zulkarnain; Hendro Prabowo (Jurnal Transportasi, 2022)
Abstract The Covid-19 pandemic has had an impact on various sectors of life, including education, the economy, and transportation. There has been a change in the mobility pattern of transportation users, including users of public transportation. One group of users of multimodal transportation, namely employees who work from the office or WFO, experienced changes in mobility due to concerns about the risk of being exposed to the Covid-19 virus when using public transportation. This study aims to examine changes in the mobility of multimodal users before and during the Covid-19 pandemic, which was carried out using a phenomenological qualitative approach through interviews. Respondents in this study were several WFO employees, who used multimodal transportation to and from work. This study shows that there is a change in the mobility of WFO employees when using multimodal transportation before and during the Covid-19 pandemic. These changes are the impact and strategies of respondents to overcome worries and feelings of insecurity when using public transportation facilities. To overcome these concerns and insecurities, respondents tried to minimize the risk of being exposed to the Covid-19 virus when using public transportation facilities. Keywords: mobility; public transportation users; multimodal; Covid-19 pandemic. Abstrak Pandemi Covid-19 berdampak pada berbagai sektor kehidupan, baik pendidikan, ekonomi, maupun transportasi. Terjadi perubahan pola mobilitas pengguna transportasi, termasuk pengguna transportasi umum. Salah satu kelompok pengguna transportasi multimoda, yaitu karyawan yang melakukan work from office atau WFO, mengalami perubahan mobilitas akibat kekhawatiran akan risiko terpapar virus Covid-19 saat menggunakan transportasi umum. Penelitian ini bertujuan untuk mengkaji perubahan mobilitas pengguna multimoda sebelum dan selama pandemi Covid-19, yang dilakukan dengan menggunakan pendekatan kualitatif fenomenologis melalui wawancara. Responden pada studi ini adalah beberapa karyawan WFO, yang menggunakan transportasi multimoda saat berangkat dan pulang kerja. Penelitian ini menunjukkan bahwa terjadi perubahan mobilitas pegawai WFO saat menggunakan transportasi multimoda sebelum dan selama masa pandemi Covid-19. Perubahan tersebut merupakan dampak dan strategi responden untuk mengatasi kekhawatiran dan perasaan tidak aman saat menggunakan fasilitas transportasi umum. Untuk mengatasi kekhawatiran dan rasa tidak aman tersebut, responden berupaya meminimalkan risiko terpapar virus Covid-19 saat menggunakan fasilitas transportasi umum. Kata-kata kunci: mobilitas; pengguna transportasi umum; multimodal; pandemi Covid-19.